ADB [videorecording] catalyst for development - Asian Development Bank (ADB Production, 1994)
Discusses the Asian Development Bank as an institution which strives to promote economic growth and alleviate poverty in the Asian-Pacific region through its lending operations, support to private sector, technical assistance and co-financing.